Imagine hope : AIDS and gay identity - Watney, Simon (Social aspects of AIDS., 2000)
Presents a chronological selection of Watney's writings from the 1990s, with new contextualising introductory and concluding essays and offers a chronicle of the changing and often confusing course of the epidemic.